The Future of AI in Dentistry: Revolutionizing Diagnosis, Treatment, and Patient Care - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming clinical practice, and dentistry is at the forefront of this digital re...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care